Pengaruh Citra dan Tata Ruang Cafe dalam Peningkatan Jumlah Pelanggan pada Caf E Ej33 di Kota Tarakan - Hidayat, Nurul; Benny Rkhan, Meily; Yoshica Izzaurajz, Imelda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The rapid development of the coffee business in Indonesia, particularly in major and minor cities, has attracted many entrepreneurs to open coffee shops. Customer impressions inside cafes are influenced by spatial arrangement, cafe image, and other factors such as products, services, and physical environment. Modern cafes offer a variety of food and beverages while creating a comfortable environment. The cafe's spatial arrangement plays a significant role in creating comfort and attraction that affect customer choices. This research focuses on Cafe EJ33 in Tarakan, North Kalimantan, which has a unique concept with spacious indoor and outdoor areas, including a VIP space. The study employs a survey method with 100 respondents to explore whether the cafe's image and spatial arrangement influence customer preferences at Cafe EJ33. The analysis results indicate a positive influence of the cafe's image on customer preferences, suggesting that Cafe EJ33 is perceived by respondents as a place that provides a positive experience and image. The study also validates the questionnaire and measures the reliability of the variables used in this research, with results supporting validity and reliability..